2019
DOI: 10.1093/molbev/msz161
|View full text |Cite
|
Sign up to set email alerts
|

Admixture between Ancient Lineages, Selection, and the Formation of Sympatric Stickleback Species-Pairs

Abstract: Ecological speciation has become a popular model for the development and maintenance of reproductive isolation in closely related sympatric pairs of species or ecotypes. An implicit assumption has been that such pairs originate (possibly with gene flow) from a recent, genetically homogeneous ancestor. However, recent genomic data have revealed that currently sympatric taxa are often a result of secondary contact between ancestrally allopatric lineages. This has sparked an interest in the importance of initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 108 publications
0
34
0
Order By: Relevance
“…To characterize the extent of phenotypic and genotypic parallelism within a system, it is necessary to rigorously demonstrate that populations adapting to similar environments (collectively referred to as an ecotype) have arisen multiple times independently. We refer the reader to our previous analyses of parallel evolution in Senecio lautus (Roda et al, 2013b;James et al, 2020) and to systems such as the marine snail, Littorina saxatilis (Quesada et al, 2007;Johannesson et al, 2010;Bierne et al, 2013;Butlin et al, 2014;Pérez-Pereira et al, 2017), and the threespine stickleback, Gasterosteus aculeatus (Colosimo et al, 2005;Chan et al, 2010;Dean et al, 2019;Marques et al, 2019) where one can find some of the strongest evidence for the independent origin of populations, and to the increasing number of potential cases of parallel evolution in plants (Foster et al, 2007;Ostevik et al, 2012;Trucchi et al, 2017;Cai et al, 2019;Konečná et al, 2019;Knotek et al, 2020).…”
Section: A Framework To Measure Parallel Evolutionmentioning
confidence: 99%
“…To characterize the extent of phenotypic and genotypic parallelism within a system, it is necessary to rigorously demonstrate that populations adapting to similar environments (collectively referred to as an ecotype) have arisen multiple times independently. We refer the reader to our previous analyses of parallel evolution in Senecio lautus (Roda et al, 2013b;James et al, 2020) and to systems such as the marine snail, Littorina saxatilis (Quesada et al, 2007;Johannesson et al, 2010;Bierne et al, 2013;Butlin et al, 2014;Pérez-Pereira et al, 2017), and the threespine stickleback, Gasterosteus aculeatus (Colosimo et al, 2005;Chan et al, 2010;Dean et al, 2019;Marques et al, 2019) where one can find some of the strongest evidence for the independent origin of populations, and to the increasing number of potential cases of parallel evolution in plants (Foster et al, 2007;Ostevik et al, 2012;Trucchi et al, 2017;Cai et al, 2019;Konečná et al, 2019;Knotek et al, 2020).…”
Section: A Framework To Measure Parallel Evolutionmentioning
confidence: 99%
“…Courtship behavioral differences often play a key role in maintaining adaptive divergence in stickleback, and this has been particularly well studied in divergent benthic–limnetic (Foster, 1995; Foster et al, 2008; Shaw et al., 2007), lake–stream (Delcourt et al., 2008; Raeymaekers et al., 2010) and japan sea anadromous—pacific ocean anadromous ecotypes (Kitano et al., 2007). Lagoon stickleback have only recently been recognized as an ecotype in their own right (Dean et al., 2019; Ravinet et al., 2015), and so their courtship behavior has not previously been investigated. We showed that lagoon males performed fewer of many of the classic stickleback courtship behaviors than males of the other two ecotypes (or sometimes none).…”
Section: Discussionmentioning
confidence: 99%
“…Anadromous fish are much larger, more heavily armored and differ from resident ecotypes in body shape and various trophic morphological traits such as gill raker number, reflecting their more pelagic lifestyle (see Figure 1 for photographs of different ecotypes). Reproductive isolation in species pairs is strong despite low levels of gene flow (Dean et al., 2019), and there is likely strong selection against hybrids, many of which probably attempt to migrate to sea without the full suite of associated traits. Hybrid fish, for example, often exhibit an intermediate lateral plate phenotype (Dean et al., 2019), which would likely make them more vulnerable to predation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fish are widely distributed in various aquatic environments such as freshwater, brackish water and seawater, and have been divided into an anadromous type and a freshwater resident (fluvial) type 1 . The freshwater type was found to have recolonized from anadromous populations after the last deglaciation approximately ~ 10,000-20,000 years ago [6][7][8][9][10][11][12][13][14][15] . Anadromous and freshwater resident stickleback populations are usually allopatric but are occasionally parapatric or sympatric 7,[16][17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%